A wrinkle in time the graphic novel - L'engle's, Madeleine (Square fish, an imprint of Macmillan Publishing Group, 2015)
"Late one night, three otherworldly creatures appear and sweep Meg Murry, her brother Charles Wallace, and their friend Calvin O'Keefe away on an extraordinary mission to save Mr. Murry, who was gone missing while doing top secret work. They travel via tesseract--a wrinkle that transports one across space and time--and discover a dark force that threatens the very safety of the universe." -- Provided by publisher